2021
DOI: 10.1242/jeb.234831
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cranial biomechanics in two lizard species: impact of variation in cranial design

Abstract: Cranial morphology in lepidosaurs is highly disparate and characterized by the frequent loss or reduction of bony elements. In varanids and geckos, the loss of the postorbital bar is associated with changes in skull shape, but the mechanical principles underlying this variation remain poorly understood. Here, we seek to determine how the overall cranial architecture and the presence of the postorbital bar relate to the loading and deformation of the cranial bones during biting in lepidosaurs. Using computer-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 101 publications
0
19
1
Order By: Relevance
“…Several previous FEA studies have investigated bite force and feeding stress in lizards. Dutel et al. (2021) measured an in vivo bite force of 211 and 314 N and ex vivo bite force of 213 and 308 N in anterior bilateral and posterior unilateral bites of Salvator merianae (skull length = 81mm).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous FEA studies have investigated bite force and feeding stress in lizards. Dutel et al. (2021) measured an in vivo bite force of 211 and 314 N and ex vivo bite force of 213 and 308 N in anterior bilateral and posterior unilateral bites of Salvator merianae (skull length = 81mm).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has used a variety of colour maps to display the results from FEAs [64]. Similarly, for palaeontological studies using other engineering tools, different colour maps have started to appear in publications.…”
Section: Discussionmentioning
confidence: 99%
“…The South American teiid lizard Salvator merrianae is of similar size and lifestyle to V. niloticus, and the two species have a comparable bite force [69]. However, the skull of Salvator differs from that of Varanus in snout structure, and in having a complete postorbital bar and weakly developed cristae cranii on the frontal.…”
Section: (E) the Evolution Of Varanid Cranial Charactersmentioning
confidence: 99%
“…However, the skull of Salvator differs from that of Varanus in snout structure, and in having a complete postorbital bar and weakly developed cristae cranii on the frontal. Dutel et al [69] found that the postorbital bar of Salvator experienced very high strain magnitudes during biting, especially in bites by the posterior teeth, and that removal of the bar significantly increased strain magnitudes in other parts of the skull. The postorbital bar is therefore important in maintaining skull integrity during biting in Salvator.…”
Section: (E) the Evolution Of Varanid Cranial Charactersmentioning
confidence: 99%
See 1 more Smart Citation